PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER TERHADAP HASIL BELAJAR MATEMATIS PESERTA DIDIK KELAS VIII SMPN 1 SIMPANG ALAHAN MATI - Nugraha, Jessycha Tri (Jurnal Edukasi dan Penelitian Matematika, 2025)
As a benchmark to measure the extent to which it has internalized the material discussed in class, educators use learning outcomes as a benchmark. Class VIII at SMPN 1 Simpang Alahan Mati actually has relatively low scores in this regard. Factors that contribute to this are unsupportive learning models and passive learning. One model that can be used is a cooperative model known as Numbered Head Together (NHT). Using the Nonequivalent Posttest-Only Control Group Design, this research methodology includes descriptive research and quasi-research. A P-value = 0.000 with α = 0.05 was obtained from the test analysis results conducted using the t-test. Based on data analysis, the NHT model produced better learning outcomes than the conventional method, and quiz scores increased when using the NHT model.Keywords–Numbered Head Together, Learning outcomes, Conventional Learning Model